Strategi Pengembangan Kampung Topeng Malang sebagai Kampung Wisata Budaya - Magvira Ardhia Pratiwi; Novi Sunu Sri Giriwati; Yusfan Adeputera Yusran; Herry Santosa (RUAS, 2022)
The Desaku Menanti Program is a government program that is relocating the homeless to a new village as a tourist destination, one of the results of the program is the Mask Tourism Village. The potential of Malangan Mask cultural characteristics to be the main attraction of this tour was able to attract many visitors at the beginning of its inauguration. But it didn't last long, now the village is deserted and no one even comes. This research will examine how the strategy of developing Kampung Mask as a cultural tourism village. The method used is a mix-method, namely a qualitative method with SWOT and a quantitative method with an analysis of tourist needs preferences for cultural tourism villages with questionnaire. The results of the study indicate that this village needs to dig deeper into the concept of culture, improve the quality of its facilities, and also have a well-managed tourism management with community participation. Based on the analysis of tourist preferences, it was found that if it was necessary to add facilities and other cultural attractions, 49% of respondents chose the visual characteristics of settlements with traditional buildings and accommodation was villas in nature.